Community structure of brachyuran crab in Setiu Lagoon, Terengganu - Zakirah Mohamad Taufek
A study on the diversity and community structure of Brachyuran crab was conducted in the Setiu lagoon, Terengganu. The sampling has been done once in every two months for a year starting from July 2011 until May 2012. The study aims to investigate the abundance and community structure of Brachyuran crab in the Setiu lagoon. In addition, this study also investigated the relationship between Brachyuran crab community and selected physico-chemical parameters of waters such as salinity, pH and Dissolved oxygen) and sediment grain size and total organic matter.